2021
DOI: 10.1371/journal.pone.0245472
|View full text |Cite
|
Sign up to set email alerts
|

Exploring 3D miniatures with action simulations by finger gestures: Study of a new embodied design for blind and sighted children

Abstract: Tactile books for blind children generally contain tactile illustrations referring to a visual world that can be difficult to understand. This study investigates an innovative way to present content to be explored by touch. Following embodied approaches and evidence about the advantages of manipulations in tactile processing, we examined 3D miniatures that children explored using their middle and index fingers to simulate leg movements. This “Action simulations by finger gestures–ASFG” procedure has a symbolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Concerning the first page that required an action simulating climbing stairs by finger gestures, the matching and expected manual exploration rates were lower. Nevertheless, given that recognizing a model of a stair and producing the finger gestures have been tested in previous studies (Valente et al, , 2021 and shown to be successful, we believe that the low rates reflect children's difficulties in familiarizing themselves with the book procedures. Indeed, we suppose that an introduction page to the procedures of the book would have allowed the children to project themselves more easily in the book from the first page (e.g., a page that introduces children to ASFG and asks them to simulate the legs of a character with their two fingers).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Concerning the first page that required an action simulating climbing stairs by finger gestures, the matching and expected manual exploration rates were lower. Nevertheless, given that recognizing a model of a stair and producing the finger gestures have been tested in previous studies (Valente et al, , 2021 and shown to be successful, we believe that the low rates reflect children's difficulties in familiarizing themselves with the book procedures. Indeed, we suppose that an introduction page to the procedures of the book would have allowed the children to project themselves more easily in the book from the first page (e.g., a page that introduces children to ASFG and asks them to simulate the legs of a character with their two fingers).…”
Section: Discussionmentioning
confidence: 93%
“…In youth literature, forms and styles of illustrations are highly varied, as their primary purpose is to awaken and maintain the interest of young readers and/or to support their understanding and memorization of the story (Valente & Gentaz, 2019). Recently, studies have shown that replacing visual content with relevant textures, three-dimensional (3D) elements or manipulations would improve recognition of illustrations and story processing in tactile books (Bara et al, 2018; Mascle et al, 2022; Valente et al, 2021). In an exploratory study, Bara et al(2018) showed that the processing of information in a story was enhanced through the manipulation of miniature objects, especially in congenitally blind children.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations